Dracula untold [videorecording (DVD)] - Evans, Luke, 1979-; Cooper, Dominic, 1978-; Gadon, Sarah, 1987- (Universal Studios Home Entertainment, 2015)
As his kingdom is being threatened by the Turks, young prince Vlad Tepes must become a monster feared by his own people in order to obtain the power needed to protect his own family, and the families of his kingdom.